The diversity and distribution of fish at the port and urbanized areas of Pulau Pinang Strait, Malaysia - Muzzalifah Abd Hamid,; Amir Shah Ruddin Md Sah,; Izwandy Idris,; Siti Azizah Mohd Nor,; Mazlan Abdul Ghaffar,; Ngo, Casey Saik Peng; Shahril Mod Husin, (Universiti Kebangsaan Malaysia, 2023)
Marine fish in Malaysian waters are impacted by various stressors, including resource exploitation, urbanization and industrialization. Therefore, this study examines the fish diversity and distribution at five sampling stations with different natural processes and anthropogenic activities in the coastal waters of Pulau Pinang, Malaysia. A total of 669 fish specimens belonging to 47 species from 23 families were collected using drift nets in two sampling periods from October to November 2017 and October to November 2019. The fish abundance is determined based on the catch per unit effort, (CPUE ind/hour). Among the dominant families, Leiognathidae and Ariidae accounted for 21.22 and 14.44 of the total catch, respectively. Three fish species, namely, Eubleekeria splendens, Anodontostoma chacunda, and Pennahia anea, dominated the catches. The CPUE near the ongoing reclamation projects and landfill was lower than that of the port and industrial areas with mangrove estuaries. The dendrogram clearly differentiated the fish species composition between the reclamation sites and natural shorelines. Given no previous research on the fish distribution along the Pulau Pinang strait featuring different habitat types, this study therefore serves as a contemporary fish assemblage for future research and surveys.